Open or endovascular revascularization in the treatment of acute lower limb ischaemia. Issue 12 (25th July 2018) - Grip, O; Wanhainen, A; Michaëlsson, K; Lindhagen, L; Björck, M
Abstract: Background: Consensus is lacking regarding intervention for patients with acute lower limb ischaemia (ALI). The aim was to study amputation-free survival in patients treated for ALI by either primary open or endovascular revascularization. Methods: The Swedish Vascular Registry (Swedvasc) was combined with the Population Registry and National Patient Registry to determine follow-up on mortality and amputation rates. Revascularization techniques were compared by propensity score matching 1 : 1. Results: Of 9736 patients who underwent open surgery and 6493 who had endovascular treatment between 1994 and 2014, 3365 remained in each group after propensity score matching. Results are from the matched cohort only. Mean age of the patients was 74·7 years; 47·5 per cent were women and mean follow-up was 4·3 years. At 30-day follow-up, the endovascular group had better patency (83·0 versus 78·6 per cent; P  < 0·001). Amputation rates were similar at 30 days (7·0 per cent in the endovascular group versus 8·2 per cent in the open group; P  = 0·113) and at 1 year (13·8 versus 14·8 per cent; P  = 0·320). The mortality rate was lower after endovascular treatment, at 30 days (6·7 versus 11·1 per cent; P  < 0·001) and after 1 year (20·2 versus 28·6 per cent; P  < 0·001). Accordingly, endovascular treatment had better amputation-free survival at 30 days (87·5 versus 82·1 per cent; P  < 0·001) and 1 year (69·9 versus 61·1 per cent; P  < 0·001). The number needed to treat to prevent one death within the first year was 12 with an endovascular compared with an open approach. Five years after surgery, endovascular treatment still had improved survival (HR 0·78, 99 per cent c.i. 0·70 to 0·86) but the difference between the treatment groups occurred mainly in the first year. Conclusion: Primary endovascular treatment for ALI appeared to reduce mortality compared with open surgery, without any difference in the risk of amputation. Abstract : Endovascular may save lives